Equity Research of Vodafone Group PLC - Santos Simões, João (2024)
The aim of this thesis is to understand and analyze Vodafone Group Plc business and provide a recommendation for an investor. From the analysis, the investor for Vodafone would be a combination of a value investor and an income investor. The current stock price, which stands at its lowest point in the past two decades, coupled with assessments derived from discounted cash flow (DCF) and market multiples valuation methods, unequivocally indicate that the stock is significantly undervalued and possesses strong fundamentals, aligning well with the principles of value investing. Additionally, Vodafone's consistent payment of semiannual dividends, which rank among the highest on the FTSE index, makes it particularly appealing to income-oriented investors seeking stable returns.